The herpes simplex virus type 1 UL42 gene product: a subunit of DNA polymerase that functions to increase processivity. - Gottlieb, J (1990)
Genetic experiments have shown that the products of the herpes simplex virus type 1 (HSV-1) DNA polymerase (UL30) and UL42 genes are both required for viral DNA replication, and a number of studies have suggested that these two proteins specifically interact. We have confirmed and extended these findings. The viral DNA polymerase from HSV-1-infected cells has been purified as a complex containing equimolar quantities of the UL30 (Pol, the catalytic subunit) and UL42 polypeptides. Sedimentation and gel filtration analyses of this complex are consistent with the idea that the complex consists of a heterodimer of Pol and UL42. A complex with identical physical and functional properties was also purified from insect cells coinfected with recombinant baculoviruses expressing the two polypeptides. Therefore, the formation of the Pol-UL42 complex does not require the participation of any other HSV-encoded protein. We have compared the catalytic properties of the Pol-UL42 complex with those of the isolated subunits of the enzyme purified from recombinant baculovirus-infected insect cells. The specific activity of the catalytic subunit alone was nearly identical to that of the complex when assayed on activated DNA. When assayed on a defined template such as singly primed M13 DNA, however, the combination of Pol and UL42 utilized fewer primers and formed larger products than Pol alone. Template challenge experiments demonstrated that the Pol-UL42 complex was more highly processive than Pol alone. Our data are consistent with the idea that the UL42 polypeptide is an accessory subunit of the DNA polymerase that acts to increase the processivity of polymerization.